Posterior tibial slope modification in osteoarthritis knees with different ACL conditions: Cadaveric study of fixed-bearing UKA - Nath Adulkasem (2019)
© The Author(s) 2019. Unicompartmental knee arthroplasty (UKA) in anterior cruciate ligament deficiency (ACLD) has been debated for decades after the development of highly cross-linked polyethylene. This study aims to evaluate the effect of posterior tibial slope on restoring adequate knee stability and flexion after UKA in patients with ACLD. A total of 15 fresh cadaveric knees were divided into three groups: intact ACL, partial ACLD, and complete ACLD. Fixed-bearing UKAs including 3-D-printed tibial inserts with the slopes ranging from 3° to 12° were performed using computer-assisted navigation. Blinded evaluation of knee motion and anterior knee translation with knees flexed 20° and 90° was conducted using KT-arthrometry and stress radiography. A 1° slope increase translated the knees anteriorly by 0.85 mm and 0.76 mm in 20° and 90° of knee flexion for a complete ACLD (R = 0.7 and 0.8, respectively, p < 0.001) compared to 0.5–0.6 mm for the normal and partial ACLD groups, respectively. Setting a slope of 5–8° of UKA for an intact ACL maintained both the stability and the motion of native knees. No significant changes of knee translation and flexion ability were observed after leveling the slopes at 5–7° and 5–6° for partial and complete ACLD, respectively (p > 0.05 for all comparisons). In conclusion, UKA in complete ACLD knees is challenging since 1° of slope change nearly doubles the degree of knee translation compared to ACL-intact knees. The optimum posterior tibial slopes for fixed-bearing UKA patients with partial and complete ACLD are 5–7° and 5–6°, respectively.